Two new species of the genus Heterothera Inoue, 1943 (Lepidoptera, Geometridae, Larentiinae) from Xizang, China - Yang, Shuang; Yu, Xia; Viidalepp, Jaan; Pan, Zhaohui (Zootaxa, 2026)
The genus Heterothera Inoue, 1943 has not been reported previously in Xizang, and this paper documents three species collected from Sejila Mountain in Bayi District and Motuo county (Mêdog), Xizang. Among them, Heterothera sejilaensis Pan & Yang, sp. nov. and Heterothera pailongensis Pan & Yang, sp. nov. are described as new species, and Heterothera hoenei Choi, 1998 is described as a new record from Xizang. The adults and genitalia of the new species and their related species have been illustrated. Viidaleppia Inoue is restored from synonymy as a subgenus of Heterothera Inoue for quadripectinate species.